Orcinol glucoside improves the depressive‐like behaviors of perimenopausal depression mice through modulating activity of hypothalamic–pituitary–adrenal/ovary axis and activating BDNF‐ TrkB‐CREB signaling pathway. (11th August 2021) - Li, Junlong; He, Pingya; Zhang, Jian; Li, Ning
Abstract : Orcinol Glucoside (OG), a phenolic glucoside isolated from C. orchioides, showed the antidepressant‐like effect on chronic unpredictable mild stress (CUMS)‐induced rats previously. This study was designed to determine whether OG could improve the depressive‐like symptoms of perimenopausal depression (PMD) and the possible mechanisms involved. This research was performed on a PMD mice model established by a two‐steps method of ovariectomy (OVX) followed CUMS. OG treatment effectively improved the depressive‐like behaviors of OVX‐CUMS mice, as indicated by increased sucrose intake in sucrose preference test (SPT), reduced immobility time in forced swimming test (FST), and tail suspension test (TST), lower frequency of grooming and defecation, increased actions of rearing, and prolonged duration in the center in open field test (OFT). OG treatment alleviated the OVX‐CUMS induced dysfunction of hypothalamic–pituitary‐ovarian (HPO) axis by increased serum estradiol (E2) and decreased ovarian hormones follicle stimulating hormone (FSH), luteinizing hormone (LH), and gonadotropin‐releasing hormone (GnRH) in serum. Meanwhile, OG reversed the hyperactivity of hypothalamic–pituitary–adrenal (HPA) axis as evidenced by decreased CORT and ACTH in serum, reduced as well as the mRNA and protein expression of corticotropin‐releasing hormone (CRH) in hypothalamus and hippocampus. Moreover, OG up‐regulated the protein expression of BDNF, TrkB, and phosphorylation level of CREB and ERK1/2 in hippocampus. These findings demonstrated that OG improves depressive behaviors of OVX‐CUMS mice by modulating of HPO/HPA axis dysfunction, and activating BDNF–TrkB‐CREB signaling pathway.